General Motor Holden's closure in Playford, South Australia: Analysis of the policy response and its implications for health. Issue 1 (20th June 2019) - Browne‐Yung, Kathryn; Ziersch, Anna; Baum, Fran; Friel, Sharon; Spoehr, John
Abstract: Deindustrialisation and the closure of automotive manufacturing can differentially affect the socioeconomic prospects of workers and their communities, and contribute to social and health inequity. We used Bacchi's problematisation approach to examine the South Australian (SA) Labor government's policy responses to the General Motors Holden (GMH) Elizabeth plant closure announcement. We focused on the way that these policy responses framed the 'problem' of this major economic shock, particularly the extent to which potential social and health equity consequences were addressed. We found a narrow focus on economic strategies, neglecting the compounding impact of poverty in Playford, which may exacerbate health inequity. The community effects from the GMH closure remain uncertain and may be delayed for several years. SA requires better integrated social and economic policies to minimise social and health inequalities, as the consequences of the car manufacturing loss are realised. Abstract : An analysis of how the South Australian government's policy response to the General Motors Holden closure addressed potential health equity for the affected community.